Biomechanical evaluation of exoskeleton use on loading of the lumbar spine. (April 2018) - Weston, Eric B.; Alizadeh, Mina; Knapik, Gregory G.; Wang, Xueke; Marras, William S.
Abstract: The objective of this study was to investigate biomechanical loading to the low back as a result of wearing an exoskeletal intervention designed to assist in occupational work. Twelve subjects simulated the use of two powered hand tools with and without the use of a Steadicam vest with an articulation tool support arm in a laboratory environment. Dependent measures of peak and mean muscle forces in ten trunk muscles and peak and mean spinal loads were examined utilizing a dynamic electromyography-assisted spine model. The exoskeletal device increased both peak and mean muscle forces in the torso extensor muscles (p < 0.001). Peak and mean compressive spinal loads were also increased up to 52.5% and 56.8%, respectively, for the exoskeleton condition relative to the control condition (p < 0.001). The results of this study highlight the need to design exoskeletal interventions while anticipating how mechanical loads might be shifted or transferred with their use. Highlights: Lumbar spine loads were assessed for an exoskeleton designed for hand tool use. The exoskeleton increased peak and mean torso muscle forces and spinal loads. Exoskeletons must be designed considering loads placed onto multiple joints.